Cover. Issue 5 (27th September 2018) - Bishop, Madison R.; Shah, Amit; Shively, Melissa; Huskey, Anna L. W.; Omeler, Sophonie M.; Bilgili, Erin P.; Jackson, Ebony; Daniell, Kathleen; Stallworth, Elizabeth; Spina, Stephanie; Shepp, Kasey; Bergstresser, Sydney; et al.
Abstract : The cover image, by Madison R. Bishop et al., is based on the Original Article Establishment of the Alabama Hereditary Cancer Cohort ‐ strategies for the inclusion of underrepresented populations in cancer genetics research, DOI:10.1002/mgg3.443 . Image Credit: Nancy Merner, Principle Investigator – The Gene Machine.